CAPACITY BUILDING UNTUK UMKM NAIK KELAS - Badriyah; Syafrial, Herry; Setiawan; Susbiyantoro; Sambodja, Edy; Febriyanti (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
This positive trend needs to continue to maintain its growth so that the MSME sector on a large scale is able to overcome the problem of unemployment in Indonesia. MSMEs are part of the independent Indonesian economy and have great potential to improve people's welfare seen from the three roles of MSMEs in the Indonesian economy, including a means of equalizing the economic level of the small people, a means of alleviating poverty and a means of earning foreign exchange for the country. MSME business with small capital is possible for anyone to do. MSME businesses must develop and be known by the wider community, so that their products can be known and consumed by the wider community. MSME branding aims to involve creating and maintaining a strong and positive brand image in the eyes of consumers. Branding is an effort to build an identity that differentiates a product or service from its competitors. The government is committed to increasing the contribution of micro, small and medium enterprises to the economy. However, the results of various MSME empowerment programs that have been implemented by Ministries and Institutions have not been optimal. Therefore, synchronization and harmonization of MSME empowerment programs is needed to increase the effectiveness of program implementation, so that it can increase the contribution of MSMEs to the economy. Through a community service program called